2012
DOI: 10.1111/j.1525-142x.2011.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

How was the notochord born?

Abstract: More than 550 million years ago, chordates originated from a common ancestor shared with nonchordate deuterostomes by developing a novel type of larva, the "tadpole larva." The notochord is the supporting organ of the larval tail and the most prominent feature of chordates; indeed, phylum Chordata is named after this organ. In this review, we discuss the molecular mechanisms involved in the formation of the notochord over the course of chordate evolution with a special emphasis on a member of T-box gene family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 179 publications
(228 reference statements)
1
72
0
Order By: Relevance
“…The T gene belongs to the family of T-box genes that encode transcription factors consisting of transcriptional activator and/or repressor domains and a DNA-binding T-box domain in many eukaryotic species including vertebrates and invertebrates (Satoh et al 2012). The T protein is essential for development of the notochord and mesoderm formation in the primitive streak during early embryonic vertebrate development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T gene belongs to the family of T-box genes that encode transcription factors consisting of transcriptional activator and/or repressor domains and a DNA-binding T-box domain in many eukaryotic species including vertebrates and invertebrates (Satoh et al 2012). The T protein is essential for development of the notochord and mesoderm formation in the primitive streak during early embryonic vertebrate development .…”
Section: Discussionmentioning
confidence: 99%
“…The murine brachyury (T) gene with its mutant alleles was the first gene that was identified and positionally cloned based on a genetic defect only, the long-known brachyury resulting in vertebral and spinal defects (Dobrovolskaia-Zavadskaia 1927;Herrmann et al 1990). Numerous subsequent studies confirmed that the coordinated expression of the T gene during gastrulation is essential for appropriate notochord, neural tube, and mesoderm development (Chesley 1935;Pennimpede et al 2012;Satoh et al 2012). Recently, the T gene has gained interest because of its association with the human chordoma, a sporadic and hereditary tumor originating from relicts of the notochord (Yang et al 2009;Pillay et al 2012;Nibu et al 2013).…”
mentioning
confidence: 99%
“…The organ that best characterizes chordates is the notochord, an organ that supports the beating of the muscular tail of fish-like larvae or adults [1, 3, 4]. The T-box family transcription-factor gene, Brachyury , plays an essential role in notochord formation [5]. In ascidians (urochordates), for example, Brachyury is expressed exclusively in primordial embryonic notochord cells [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Brachyury is not specific to chordates, but is present in most metazoans, including non-chordate deuterostomes [5, 10]. Beside paralogs derived from ancient whole genome duplication (referred to as “ohnologs”), Brachyury is usually present as a single copy, with some exceptions ( Hydra [11], calcisponge [12], and cephalochordates (see below)), and is expressed around the blastopore during gastrulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation